A simple procedure for isolation, identification and characterization of Vibrio cholerae from clinical samples - PARIMAL DUA; AMIT KARMAKAR; KUNAL DUTTA; CHANDRADIPA GHOSH (International Journal of Pharma and Bio Sciences, 2017)
Cholera is caused by Vibrio cholerae, which is a major health problem in several developing countries. Out of 147 diarrheal stool samples collected during one year period (2013) from patients with acute diarrhea admitted to the hospital, 71 cases were positive for Vibrio cholerae. In the present study, a direct multiplex PCR was developed targeting the 16S rRNA, ompW, rfbO1and rfbO139 genes for confirmation of Vibrio cholerae and its serogrouping. Interestingly, all the clinically isolated strains of Vibrio cholerae belong to non-O1/non-O139 serogroup. The phenotypic characteristics of the clinical strains of Vibrio cholerae were examined. All the isolates of Vibrio cholerae were positive for most of the biochemical reaction. Variable results were obtained in the Voges-Proskauer test. The PCR assay can be very useful for rapid surveillance of Vibrio cholerae for confirmation of clinical isolates.